Technological Prospection for Organic Waste Composting Processes - Araújo, Camila Cruz de Oliveira (2020)
Composting is a technique applied to accelerate the decomposition of organic waste. After the process, the residue rich in organic compounds and nutrients is used as organic fertilizer for agriculture. Composting processes bring numerous environmental and economic benefits, highlighting the reduction of environmental impact with the reduction of solid waste and the generation of technological innovations. The aim of this study was analyze the innovations in composting process using technological prospection searching for patents associated with organic waste composting processes. A search done in the European Patent Database (Espacenet) used the worldwide database found 15,170 patents, being 12,131 Chinese publications. It was found that Brazil is incipient both in the number of patents and in usage practices. However, as a world agricultural power, it has favorable conditions for the development of new technologies related to composting processes.